Dinamika Pembelajaran Kitab Kuning dalam Membentuk Karakter Religius Santri di Pondok Pesantren Wali Aminah Ngasem Jombok Ngoro Jombang - Pangestu, Ali Akbar Putra; Said, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the formation of religious character in students through the study of yellow books in boarding schools. Pengajaran Kitab Kuning, yang merupakan metode tradisional, memegang peranan penting dalam pembentukan karakter religius santri. Di sisi lain, pesantren dihadapkan pada tekanan modernisasi yang menuntut adaptasi tanpa meninggalkan tradisi yang telah lama dipelihara. The research aims to: (1) to describe the dynamics of the teaching of the yellow book in Pondok Pesantren Wali Aminah Ngasem Jombok Ngoro Jombang, and (2) to identify the factors that support and hinder the process. The study uses a qualitative descriptive method with a case study approach. Data collection was conducted through observation, interviews, and documentation. Data analysis is based on Miles and Huberman's interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The validity of the data was tested through credibility, transferability, dependability, and confirmability checks. The results of the study show that: (1) the study of the yellow book in the boarding school is carried out by combining the classical boarding school curriculum and the use of technology in response to the development of the times; and (2) the supporting factors include the competence of the teacher, the enthusiasm of the students, the teaching materials, the boarding school environment, and the role model (uswatun hasanah), while the limiting factors include the limited ability of the teacher in the field of technology, the differences in the background and the level of understanding of the students, the emotional changes of the students, and the influence of social interaction among the students.